2022
DOI: 10.1177/20552076221083119
|View full text |Cite
|
Sign up to set email alerts
|

Ingestible electronic sensors to measure instantaneous medication adherence: A narrative review

Abstract: Objective Medication nonadherence contributes to significant morbidity and mortality worldwide. While many techniques to measure adherence exist, digital pill systems represent a novel, direct method of measuring adherence and a means of providing instantaneous adherence supports. In this narrative review, we discuss digital pill system research based on clinical trials and qualitative investigations conducted to date and potential future applications of digital pill system in medication adherence measurement.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…A novel platform comprises ingestible sensors implanted in medications for TB, HCV, HIV, and other medical conditions where adherence is crucial to avoid significant morbidity and mortality [ 62 ]. Upon ingestion, the sensor interacts with the patient’s gastric fluid sending a signal transmitted to a monitor adhered to the patient’s skin, which sends a signal to the patient’s smartphone allowing sharing of the information with the patient’s physician.…”
Section: Using First-generation Digital Platforms For Improving the E...mentioning
confidence: 99%
“…A novel platform comprises ingestible sensors implanted in medications for TB, HCV, HIV, and other medical conditions where adherence is crucial to avoid significant morbidity and mortality [ 62 ]. Upon ingestion, the sensor interacts with the patient’s gastric fluid sending a signal transmitted to a monitor adhered to the patient’s skin, which sends a signal to the patient’s smartphone allowing sharing of the information with the patient’s physician.…”
Section: Using First-generation Digital Platforms For Improving the E...mentioning
confidence: 99%
“…Previous investigations have demonstrated the feasibility of utilizing a DPS to measure medication adherence in the context of multiple disease states, including hepatitis C, hypertension, and HIV pre-exposure prophylaxis. [13] Prior studies conducted among TB patients in the US have demonstrated high DPS accuracy in detecting ingestion events and user acceptance of the technology. [14,15] Despite the demonstrated feasibility of DPS technology, however, it remains unclear whether the DPS can be implemented for ATT adherence monitoring in India, given key differences in the cultural context of adherence monitoring, availability of smartphone infrastructure, and a lack of documented perspectives of key stakeholders surrounding patient privacy in the context of TB and ATT.…”
Section: Introductionmentioning
confidence: 99%
“…Chai et al systematized 18 pilot clinical trials of digital pills in the treatment of HIV, hepatitis C, solid organ transplantation, tuberculosis, schizophrenia, cardiovascular disease, and acute fractures ( Chai et al, 2022 ). Studies typically included up to 50 patients, some between 120 and 288 individuals, and they lasted from 1 week to 6 months.…”
Section: Introductionmentioning
confidence: 99%